2022
DOI: 10.1002/edm2.359
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between polycystic ovary syndrome and hypothyroidism on serum testosterone, oxidative stress and StAR gene expression in female rats

Abstract: Introduction Endocrine disorders such as polycystic ovary syndrome (PCOS) and hypothyroidism can cause infertility. There are evidence that they happen jointly in some circumstances. It still remains unknown, how these two illnesses interact and influence the body. Methods Accordingly, a five‐group was designed, first is the control group, followed by the PCOS group. Estradiol valerate (EV) induced PCOS, the second group had only PCOS and the third, fourth and fifth groups were given varied dosages of propylth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Furthermore, a recent study has reported significantly increased expression of StAR gene in PCOS rat models compared to the control group 130 . The study also showed a positive correlation between StAR gene expression and serum testosterone levels 130 .…”
Section: Hyperandrogenismmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, a recent study has reported significantly increased expression of StAR gene in PCOS rat models compared to the control group 130 . The study also showed a positive correlation between StAR gene expression and serum testosterone levels 130 .…”
Section: Hyperandrogenismmentioning
confidence: 96%
“…Furthermore, a recent study has reported significantly increased expression of StAR gene in PCOS rat models compared to the control group 130 . The study also showed a positive correlation between StAR gene expression and serum testosterone levels 130 . These studies indicate that alterations in the steroidogenesis pathway after exposure to excess androgen could be due to changes in the expression pattern of the StAR gene.…”
Section: Hyperandrogenismmentioning
confidence: 96%